Financial sector reforms and India's economic development - Mujumdar, N. A. (Delhi : Academic Foundation, 2002)
Authored by some of the eminent economists and financial experts including top bankers, these two volumes together present an overview of some of the challenging issues.
Includes bibliographical references.
oif 12/02/15
Loans
Keywords: Banks and banking; Monetary policy; Financial institutions; Financial sector reforms; Economic development; India